Corrosion-resistant self-repairing metal fastener and preparation method

By using a combination design of zinc alloy matrix and functional composite coating on the metal fastener, the problems of matrix corrosion and coating failure in the prior art are solved, and long-term anti-corrosion and self-repair functions are achieved, which improves the reliability and service life of metal fastener.

CN120119246AInactive Publication Date: 2025-06-10GUANGZHOU AOJIN METAL PROD CO LTD
View PDF 0 Cites 5 Cited by

Patent Information

Application Number
CN202510537846.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-27
Publication Date
2025-06-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing corrosion-resistant self-repairing metal fasteners face the dual challenges of matrix corrosion and coating failure in severe corrosion environments, and the release of corrosion inhibitors is uncontrollable, and the self-repairing ability after damage is lacking.

Method used

The combination design of zinc alloy matrix and functional composite coating is adopted. The coating is composed of a nanopassivation layer, a sustained release corrosion protection layer and a self-healing functional layer. The nanopassivation layer reduces the electrochemical activity of the substrate surface through a phosphate-silane composite conversion film, the sustained-release anti-corrosion layer uses gradient pore size mesoporous silica to achieve dynamic release of corrosion inhibitor, and the self-healing functional layer achieves intelligent repair through mechanical trigger type and pH trigger type microcapsules.

Benefits of technology

It realizes long-term anti-corrosion and self-repair functions in harsh environments, improves the reliability and service life of metal fasteners, and solves the problems of easy peeling of traditional coatings and uncontrollable release of corrosion inhibitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005378544730000121
    Figure BDA0005378544730000121
  • Figure BDA0005378544730000131
    Figure BDA0005378544730000131
  • Figure BDA0005378544730000141
    Figure BDA0005378544730000141
Patent Text Reader

Abstract

The invention relates to the technical field of metal surface protection, and discloses a corrosion-resistant self-repairing metal fastener and a preparation method thereof.The corrosion-resistant self-repairing metal fastener comprises a zinc alloy matrix, a nanometer passivation layer, a slow-release corrosion-resistant layer and a self-repairing functional layer, and the nanometer passivation layer, the slow-release corrosion-resistant layer and the self-repairing functional layer sequentially wrap the zinc alloy matrix; the zinc alloy matrix consists of Al, Cu, Mg, Ce and Zn; the nano passivation layer adopts zinc phosphate / silane composite sol to construct a Si-O-P covalent bond network, and plasma is combined to graft epoxy groups to enhance the interface bonding strength; the slow-release anti-corrosion layer is used for loading a pH response type benzotriazole derivative through gradient aperture mesoporous silica, so that the dynamic controlled release of a corrosion inhibitor is realized; the self-repairing functional layer adopts a synergistic effect of a mechanical triggering type sulfydryl siloxane microcapsule and a pH triggering type EDTA chelating agent microcapsule to form a physical plugging-chemical passivation dual-mode repairing mechanism. Through four-stage cooperation of matrix modification, interface strengthening, slow-release regulation and control and intelligent repair, the corrosion resistance of the corrosion-resistant self-repairing metal fastener in a complex environment is remarkably enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metal surface protection, and specifically to a corrosion-resistant self-healing metal fastener and a preparation method thereof. Background Art

[0002] A corrosion-resistant self-healing metal fastener has been facing the dual challenges of matrix corrosion and coating failure in harsh corrosion environments in fields such as ocean engineering and automobile manufacturing for a long time.

[0003] Existing protection technologies mostly rely on single-functional coatings or alloy composition adjustments, and it is difficult to cope with dynamically changing corrosive media and the action of complex stresses. Due to the lack of an adaptive repair mechanism in the traditional coating system, corrosion spreads rapidly after physical damage, and the interfacial bonding strength is insufficient, which is prone to cause coating peeling, resulting in a significant reduction in the protection life.

[0004] In addition, conventional corrosion inhibitor loading technologies have problems such as burst release or premature depletion, and long-term controlled release cannot be achieved. Moreover, the high-temperature curing process and high VOC emissions further restrict the requirements of green manufacturing.

[0005] The current process has not yet broken through the synergistic optimization among matrix corrosion resistance, interfacial stability, and coating intelligent response, which restricts the reliability and service life of a corrosion-resistant self-healing metal fastener under complex working conditions. Summary of the Invention

[0006] Aiming at the deficiencies of the prior art, the present invention provides a corrosion-resistant self-healing metal fastener and a preparation method thereof, which solve the problems of insufficient matrix corrosion resistance, easy peeling of the coating interface, uncontrollable release of corrosion inhibitors, and lack of self-healing ability after damage in the existing protection technology of a corrosion-resistant self-healing metal fastener.

[0007] To achieve the above objectives, the present invention is realized through the following technical solutions: The first aspect of the present invention provides a corrosion-resistant self-healing metal fastener, including: A zinc alloy matrix; A composite coating covering the surface of the matrix, and the composite coating sequentially includes from the inside to the outside: A nano-passivation layer, a phosphate-silane composite conversion film; A slow-release anti-corrosion layer, an aqueous epoxy resin layer containing mesoporous silica particles and a pH-responsive corrosion inhibitor; A self-healing functional layer, a fluorocarbon resin layer containing mechanically triggered microcapsules and pH-triggered microcapsules.

[0008] Through the synergistic effect of zinc alloy matrix modification, functional composite coating design, and dynamic protection mechanism, the present invention realizes long-term anti-corrosion and self-healing functions in harsh environments.

[0009] The zinc alloy substrate is based on Zn-Al-Cu-Mg. By adding trace rare earth cerium (Ce), a refined grain structure is formed. The rare earth elements react preferentially with impurity elements (such as Fe, Pb) in the alloy to form stable compounds, reducing the electrochemically corrosive active sites at the grain boundaries. Meanwhile, the oxidation product of Ce can be adsorbed on the substrate surface to form an initial passivation layer, providing a low-defect interface for the bonding of the subsequent composite coating.

[0010] The nano-passivation layer covering the substrate surface is composed of a phosphate-silane composite conversion film. Zinc phosphate and silane molecules form a nano-scale dense network structure through a sol-gel reaction. Its mechanism of action is reflected in two aspects: The nano-scale film layer (200 - 500 nm) can effectively block the penetration paths of water molecules, Cl - and other corrosive media; The silanol groups (-Si-OH) in the silane molecules form chemical bonds with the substrate metal oxides (such as ZnO), and the passivation effect of zinc phosphate further reduces the electrochemical activity of the substrate surface.

[0011] In particular, epoxy groups are grafted onto the surface of the passivation layer through plasma treatment, enabling it to form chemical bonds with the subsequent epoxy resin coating rather than simple physical adsorption, significantly enhancing the interfacial bonding strength.

[0012] The slow-release anti-corrosion layer is based on waterborne epoxy resin and embedded with mesoporous silica particles with a gradient pore size. Its innovative mechanism lies in: The gradient pore size design (10 - 15 nm on the surface layer, 5 - 8 nm on the bottom layer) enables the loaded benzotriazole derivative corrosion inhibitor to exhibit the characteristics of "rapid initial release - continuous slow release in the later stage". When corrosive media invade the coating, the large-pore mesopores on the surface layer preferentially release high-concentration corrosion inhibitors to inhibit the spread of corrosion, while the small-pore mesopores on the bottom layer maintain long-term protection.

[0013] Benzotriazole derivatives can dissociate into active ions in acidic (pH < 4) or alkaline (pH > 9) environments and selectively adsorb on the metal surface defects to form a protective film.

[0014] The self-healing functional layer triggers the repair behavior through double signals of mechanical damage and chemical corrosion. Its core innovation lies in: the thiol-siloxane prepolymer wrapped in a polyurea formaldehyde shell ruptures when the coating is scratched by external force, and the released prepolymer reacts with water vapor in the environment to form a hydrophobic silicon oxide film, physically blocking the diffusion path of corrosive media.

[0015] When local corrosion causes abnormal pH in the micro-region, the polyacrylic acid-chitosan composite shell dissolves, releasing the EDTA derivative chelating agent, which preferentially combines with Zn 2+ to form a stable complex, inhibiting the anodic dissolution of the zinc alloy.

[0016] The -SH groups in mercapto siloxane undergo a cross-linking reaction with benzotriazole corrosion inhibitor molecules to form a composite protective film with both hydrophobicity and corrosion inhibition functions, achieving dual protection of "physical isolation - chemical passivation".

[0017] Preferably, the zinc alloy substrate comprises the following components in mass percentage: Al 4.5 - 5.5%, Cu 0.8 - 1.2%, Mg 0.4 - 0.6%, Ce 0.05 - 0.2%, and the balance is Zn and inevitable impurities; among them, the inevitable impurities include Fe < 0.02%, Pb < 0.005%, and Sn < 0.002%.

[0018] Preferably, the nano-passivation layer comprises the following components in mass percentage: Zinc phosphate 2.0 - 4.0%, silane coupling agent 3.0 - 5.0%, and the balance is deionized water; Its ratio range is designed based on the following co-film-forming mechanism: 1. Zinc phosphate, as the core component of passivation, plays a role through the following paths during the sol-gel process: Zinc phosphate reacts with ZnO / Zn(OH) on the surface of the zinc alloy substrate 2 to generate Zn 3 (PO 4 ) 2 ·4H 2 O (hopeite) crystals, which cover the surface defects of the substrate and inhibit the anodic dissolution reaction.

[0019] When the mass percentage of zinc phosphate ≥ 2.0%, the PO 4 3- ions hydrolyzed therefrom can serve as nucleation sites to promote the orderly polycondensation of silane molecules; however, when the mass percentage exceeds 4.0%, the zinc phosphate particles are prone to agglomeration, resulting in micro-cracks in the passivation film.

[0020] 2. The mass percentage (3.0 - 5.0%) of the silane coupling agent (such as γ-aminopropyltriethoxysilane) improves the performance of the passivation film through dual effects: The Si-OH groups hydrolyzed from the silane form Si-O-M (M = metal) covalent bonds with the matrix metal oxides (such as Al 2 O 3 、ZnO), and at the same time, form hydrogen bonds with the surface of the zinc phosphate particles to form a "zinc phosphate - silane" interpenetrating network structure.

[0021] When the mass percentage of the silane is less than 3.0%, the cross-linking degree of the sol is insufficient, and the porosity of the film layer > 15%; while when the mass percentage > 5.0%, the viscosity of the sol is too high, resulting in uneven thickness of the passivation film.

[0022] Preferably, the silane coupling agent is selected from at least one of γ-aminopropyltriethoxysilane (KH550) and γ-glycidoxypropyltrimethoxysilane (KH560).

[0023] Preferably, the slow-release anti-corrosion layer comprises the following components in mass percentage: Waterborne epoxy resin matrix 60-75%, gradient pore size mesoporous silica particles 15-25%, benzotriazole derivative corrosion inhibitor 3-8%, and the balance being a dispersion aid and a solvent.

[0024] Its ratio design realizes the dynamic anti-corrosion function through the following synergistic mechanism: 1. The mesoporous silica particles realize the staged release of the corrosion inhibitor through the gradient pore size design (10-15 nm on the surface layer and 5-8 nm on the bottom layer): Initial rapid release: The large pore size mesopores (10-15 nm) on the surface layer rapidly release a high concentration of benzotriazole derivatives at the initial stage of corrosion, quickly inhibiting the expansion of local corrosion; Subsequent continuous slow release: The small pore size mesopores (5-8 nm) on the bottom layer slowly release the corrosion inhibitor through capillary action to maintain the long-term protection effect.

[0025] 2. The benzotriazole derivative corrosion inhibitor plays a dynamic anti-corrosion role through the following paths: In an acidic (pH < 4) or alkaline (pH > 9) environment, benzotriazole molecules dissociate into active anions (C 6 H 4 N 3 - ), which are preferentially adsorbed on the metal surface defects to form a monomolecular protective film; The carboxyl group (-COOH) or sulfonic acid group (-SO 3 H) of the derivative side chain forms a stable complex with Zn 2+ / Al 3+ to block the electrochemical corrosion path.

[0026] When the proportion of the corrosion inhibitor is 3-8%, its loading amount accounts for 8-12% of the mesoporous pore volume, avoiding the collapse of the mesoporous structure or premature leakage caused by excessive loading.

[0027] 3. The functions of the dispersion aid (such as BYK-111, with a proportion ≤ 2%) and the solvent (such as a water / ethanol mixture) include: Preventing the aggregation of mesoporous silica through electrostatic repulsion to ensure the uniformity of the coating; The solvent completely volatilizes during the curing process and does not participate in the final coating quality composition, avoiding the negative impact of residual solvent on the coating aging resistance.

[0028] Preferably, the self-healing functional layer comprises the following components in mass percentage: 65 - 80% fluorocarbon resin matrix, 12 - 18% mechanically triggered microcapsules, 4 - 8% pH - triggered microcapsules, 1 - 3% photoinitiator, and the balance is leveling agent and solvent.

[0029] Its formulation design realizes the intelligent repair function through the following synergistic mechanisms: 1. The high fluorine content (≥60% F atoms) of the fluorocarbon resin endows the coating with excellent hydrophobicity and UV resistance. At the same time, a resin proportion of ≥65% can ensure the mechanical strength of the coating; the resin provides a uniform dispersion space for the microcapsules, avoiding coating defects caused by microcapsule sedimentation or local accumulation.

[0030] 2. The mechanically triggered microcapsules use a polyurea - formaldehyde shell to encapsulate the mercapto - siloxane prepolymer. Its mechanism of action includes: when the coating is scratched by external force, the microcapsule shell ruptures, and the released mercapto - siloxane prepolymer reacts with water vapor in the environment to form a hydrophobic silicon - oxygen film (-Si - O - Si - network), blocking the penetration path of corrosive media; The rapid oxidation cross - linking property of the mercapto group (-SH) enables the repair reaction to be completed in a short time, significantly superior to traditional epoxy resin repair agents.

[0031] Furthermore, the raw material ratio (by mass percentage) of the mechanically triggered microcapsules is as follows: Core material: 3 - mercaptopropyltrimethoxysilane (MPTMS) or mercaptopropylmethyldimethoxysilane (MMS) 80 - 85%; Shell material: urea 10 - 12%, formaldehyde solution (37%) 15 - 18%; Emulsifier: sodium dodecyl sulfate (SDS) 0.5 - 1.5%; Catalyst: hydrochloric acid (0.1mol / L) to adjust the pH to 2.5 - 3.5.

[0032] Its preparation steps are as follows: 1. Oil - phase emulsification: Mix MPTMS with 5% Span - 80 as the oil phase, add it to deionized water (oil - water ratio 1:3), and shear - emulsify at 2000rpm for 10min to form an O / W emulsion (droplet diameter 10 - 20μm); 2. Interfacial polymerization reaction: Add urea and formaldehyde solution to the emulsification system in sequence, and keep the temperature at 55 - 60°C; Dropwise add hydrochloric acid to adjust the pH to 2.8 - 3.2, and react for 4 - 6h to complete the polyurea - formaldehyde polycondensation reaction; Control the shell thickness (0.8 - 1.2μm) by regulating the urea / formaldehyde molar ratio (1:1.5); 3. Post - treatment: After the reaction is completed, centrifuge (3000 rpm, 10 min), and wash successively with ethanol and acetone to remove unreacted monomers; Dry in vacuum at 40 °C until the water content is <0.5%, to obtain microcapsules with a particle size of 20 - 50 μm.

[0033] 3. The pH-triggered microcapsules use a polyacrylic acid-chitosan composite shell to encapsulate the EDTA derivative chelating agent, and its mechanism of action includes: When local corrosion causes abnormal pH in the microzone, the shell dissolves and releases the chelating agent, which preferentially combines with Zn 2+ / Al 3+ to form a stable complex and inhibit the anodic dissolution of the metal; The EDTA derivative can chelate impurity ions such as Fe in the corrosion products 3+ to prevent its catalytic oxidation reaction.

[0034] Furthermore, the raw material ratio (by mass percentage) of the pH-triggered microcapsules is as follows; Core material: CaNa2EDTA or TEA-EDTA 70 - 75%; Shell material: chitosan (deacetylation degree ≥ 90%) 8 - 10%, polyacrylic acid (PAA, Mw = 200 kDa) 12 - 15%; Crosslinking agent: glutaraldehyde (25%) 0.5 - 1.0%; Buffer solution: acetic acid-sodium acetate (pH = 4.5).

[0035] Its preparation steps are as follows: 1. Core material dispersion: Disperse the EDTA derivative powder in a buffer solution containing 1% Tween-20, and ultrasonically treat (40 kHz, 30 min) until the particle size is ≤5 μm; 2. Layer-by-layer self-assembly: The first layer (chitosan adsorption): Mix the above dispersion with a 0.5% chitosan solution (pH = 5.0), and stir for 2 h to allow chitosan to adsorb on the surface of EDTA particles through electrostatic interaction; The second layer (PAA coating): Add 1% polyacrylic acid solution (pH = 3.0), and react at 50 °C for 1 h to form a chitosan-PAA composite layer; Crosslinking and curing: Add glutaraldehyde for crosslinking for 1 h to enhance the mechanical stability of the shell; 3. Drying treatment: After freeze-drying (-50 °C, 24 h), screen through a 200-mesh sieve to obtain microcapsules with a particle size of 30 - 80 μm.

[0036] 4. The functions of the leveling agent (such as BYK-358N, with a proportion ≤ 2%) and the solvent (such as butyl acetate) include: The leveling agent eliminates the orange peel defect during the spraying process by reducing the surface tension.

[0037] The solvent adjusts the viscosity of the coating to ensure the uniform dispersion of the microcapsules.

[0038] Preferably, the content of the mechanically triggered microcapsule is a mercapto siloxane prepolymer, and the content of the pH-triggered microcapsule is an EDTA derivative chelating agent; Among them, the mercapto siloxane prepolymer is selected from one of 3-mercaptopropyltrimethoxysilane (MPTMS) and mercaptopropylmethyldimethoxysilane (MMS); The EDTA derivative chelating agent is selected from one of calcium disodium EDTA (CaNa 2 EDTA) and triethanolamine salt of EDTA (TEA-EDTA).

[0039] The second aspect of the present invention provides a preparation method of the corrosion-resistant self-repairing metal fastener described in the first aspect, including the following steps: Step 1: Substrate preparation 1. Alloy melting: Weigh the raw materials by mass percentage: Zn 92.3 - 94.4%, Al 4.5 - 5.5%, Cu 0.8 - 1.2%, Mg 0.4 - 0.6%, Ce 0.05 - 0.2%.

[0040] Melt Zn, Al, Cu, and Mg under nitrogen protection. The melting temperature is 420 - 450°C, the stirring speed is 200 - 300 rpm, and it lasts for 15 - 20 min.

[0041] Add Zn-Ce master alloy (containing 10% Ce) and stir until completely dissolved.

[0042] 2. Die casting: Transfer the molten alloy to a preheated die-casting mold (preheating temperature 150 - 180°C) and apply a pressure of 80 - 100 MPa to form.

[0043] After demolding, perform mechanical polishing (sandpaper grit 800 - 1200) to remove surface burrs and oxide layers.

[0044] Step 2: Substrate surface pretreatment 1. Sandblasting treatment: Use 60 - 100 mesh alumina particles, sandblasting pressure 0.3 - 0.5 MPa, spray distance 10 - 15 cm, and treatment time 3 - 5 min.

[0045] Obtain a uniform micron-level pit structure with a surface roughness Ra = 3 - 5 μm.

[0046] 2. Chemical etching: Etchant composition: nitric acid (volume fraction 8 - 12%) + hydrofluoric acid (volume fraction 2 - 4%) + deionized water.

[0047] Immerse at room temperature (20 - 25°C) for 20 - 40 s to remove residual oxides and form an active surface.

[0048] 3. Formation of phosphate-silane composite conversion film: Sol preparation: zinc phosphate (mass fraction 2.0 - 4.0%) + γ-aminopropyltriethoxysilane (mass fraction 3.0 - 5.0%) + deionized water, adjust the pH value to 3.0 - 4.0.

[0049] Immersion treatment: immerse the substrate in the sol, react at 55 - 65°C for 8 - 12 min to form a composite conversion film with a thickness of 200 - 500 nm.

[0050] 4. Plasma grafting: Introduce a nitrogen / ethylene mixed gas (volume ratio 4:1 - 6:1) into the vacuum reaction chamber, with a vacuum degree of 50 - 100 Pa.

[0051] Plasma treatment parameters: power 80 - 120 W, treatment time 4 - 6 min, graft epoxy groups on the surface of the conversion film.

[0052] Step 3: Preparation of slow-release anti-corrosion layer 1. Synthesis of gradient mesoporous silica: Synthesis by template method: dissolve the template agent CTAB (mass fraction 5 - 8%) in ammonia water (0.5 - 1.5 mol / L), add tetraethyl orthosilicate (TEOS), and stir for 12 - 24 h.

[0053] Gradient pore size regulation: form a mesoporous structure with a surface pore size of 10 - 15 nm and a bottom pore size of 5 - 8 nm by adjusting the ammonia water concentration in segments.

[0054] 2. Loading of corrosion inhibitor: Dissolve benzotriazole derivatives (such as 5-carboxybenzotriazole) in ethanol (mass fraction 5 - 10%), and vacuum impregnate (-0.08 - -0.1 MPa) into the mesoporous particles, with a loading amount of 8 - 12% (pore volume ratio).

[0055] 3. Electrostatic spraying: Disperse the loaded particles in waterborne epoxy resin (solid content 35 - 45%), and add the dispersion aid BYK-111 (mass fraction 0.5 - 1.5%).

[0056] Spraying parameters: voltage 45 - 55 kV, spraying distance 20 - 25 cm, film thickness 20 - 30 μm.

[0057] Curing conditions: Curing at 75 - 85 °C in an oven for 25 - 35 min.

[0058] Step 4: Preparation of the self - healing functional layer 1. Microcapsule dispersion: Mechanically triggered microcapsules (polyurea - formaldehyde shell, containing MPTMS prepolymer) and pH - triggered microcapsules (chitosan - polyacrylic acid shell, containing CaNa 2 EDTA) are mixed at a mass ratio of 3:1.

[0059] Disperse the microcapsules in fluorocarbon resin (solid content 40 - 50%), add photoinitiator TPO (mass fraction 1 - 3%) and leveling agent BYK - 358N (mass fraction 0.5 - 1.5%).

[0060] 2. UV curing: The coated film thickness is 15 - 20 μm, and the UV curing parameters are: wavelength 360 - 370 nm, irradiation intensity 80 - 120 mW / cm 2 , time 4 - 6 min.

[0061] The surface roughness Ra of the cured coating is < 0.5 μm.

[0062] The present invention provides a corrosion - resistant self - healing metal fastener and its preparation method. It has the following beneficial effects: 1. Through the four - level collaborative design of optimizing the zinc - alloy matrix composition, strengthening the nano - passivation layer interface, dynamically regulating the slow - release anti - corrosion layer, and the intelligent response of the self - healing functional layer, the present invention realizes the full - dimensional protection of a corrosion - resistant self - healing metal fastener from the matrix to the surface. Stable structures are formed between the functional layers through chemical bonding and physical interpenetration, breaking through the technical bottleneck that the traditional single coating is prone to overall protection collapse due to interface failure.

[0063] 2. Through the slow - release kinetic regulation of gradient - pore - size mesoporous silica and the intelligent repair mechanism of dual - triggered microcapsules, the coating has the ability to respond to multiple signals such as physical damage, chemical corrosion, and environmental aging. This design can adaptively adjust the protection strategy according to the corrosion process, quickly intervene at the initial stage of damage, and continuously provide a long - term protection period of not less than 6 months.

[0064] 3. By using water - borne epoxy resin and UV - curable fluorocarbon resin as the main film - forming materials, the present invention significantly reduces the emission of volatile organic compounds. The low - temperature film - forming process of the nano - passivation layer and the UV rapid curing of the self - healing layer significantly reduce energy consumption, adapt to the existing coating production line, and meet the requirements of green manufacturing. Specific embodiments

[0065] Next, in combination with the embodiments of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.

[0066] Example 1: Step 1: Preparation of zinc alloy matrix 1. Weigh Zn 93.8%, Al 5.0%, Cu 1.0%, Mg 0.5%, Ce 0.2% (by mass percentage), melt it under nitrogen protection (435 °C), with a stirring speed of 250 rpm and a melting time of 18 min.

[0067] 2. Die casting: Preheat the mold to 160 °C, with a pressure of 90 MPa, and mechanically polish it to Ra = 0.8 μm after cooling.

[0068] Step 2: Pretreatment of the matrix surface 1. Sandblasting treatment: 80-mesh alumina particles, with a pressure of 0.4 MPa, a spraying distance of 12 cm, and a treatment time of 4 min, and the surface roughness Ra = 4.2 μm.

[0069] 2. Chemical etching: A mixed solution of 10% nitric acid + 3% hydrofluoric acid, with an etching time of 30 s, and rinse with deionized water.

[0070] 3. Composite conversion film: The sol formula is 3.5% zinc phosphate + 4.0% KH550 silane (pH = 3.5), with an impregnation temperature of 60 °C and a time of 10 min, and the film thickness is 350 nm.

[0071] 4. Plasma grafting: N 2 / C 2 H 4 = 5:1, with a power of 100 W, a treatment time of 5 min, and the grafted epoxy group density ≥ 5×10 15 / cm 2 .

[0072] Step 3: Preparation of the slow-release anti-corrosion layer 1. Synthesize gradient mesoporous silica: 6% CTAB, 1.0 mol / L ammonia water, react for 18 h, with a pore size of 12 nm on the surface layer / 7 nm on the bottom layer.

[0073] 2. Load the corrosion inhibitor: 8% ethanol solution of 5-carboxybenzotriazole, vacuum impregnation for 3 h, and the loading amount is 10%.

[0074] 3. Electrostatic spraying: The solid content of the water-based epoxy resin is 40%, the spraying voltage is 50 kV, the film thickness is 25 μm, and it is cured at 80 °C for 30 min.

[0075] Step 4: Preparation of self-healing functional layer 1. Microcapsule dispersion: 15% of mechanically triggered microcapsules (85% MPTMS content) + 5% of pH-triggered microcapsules (78% CaNa 2 EDTA content), dispersed in fluorocarbon resin (solid content 45%).

[0076] 2. UV curing: wavelength 365 nm, intensity 100 mW / cm 2 , time 5 min, film thickness 18 μm.

[0077] Example 2: Step 1: Preparation of zinc alloy substrate 1. Weigh 94.2% Zn, 4.8% Al, 0.9% Cu, 0.5% Mg, 0.1% Ce, melting temperature 425 °C, stirring speed 280 rpm, time 16 min.

[0078] 2. Die-casting pressure 85 MPa, mold preheating 170 °C, Ra = 0.6 μm after polishing.

[0079] Step 2: Substrate surface pretreatment 1. Sandblasting treatment: 100-mesh alumina, pressure 0.35 MPa, spraying distance 15 cm, Ra = 3.8 μm.

[0080] 2. Chemical etching: 9% nitric acid + 2.5% hydrofluoric acid, etching time 25 s.

[0081] 3. Composite conversion film: 2.5% zinc phosphate + 4.5% KH560 silane (pH = 3.8), dipping time 9 min, film thickness 280 nm.

[0082] 4. Plasma grafting: N 2 / C 2 H 4 = 4.5:1, power 110 W, treatment 4.5 min.

[0083] Step 3: Preparation of slow-release anti-corrosion layer 1. Mesoporous synthesis: 7% CTAB, 0.8 mol / L ammonia water, pore size 14 nm on the surface layer / 6 nm on the bottom layer.

[0084] 2. Loading inhibitor: 6% benzotriazole derivative (containing sulfonic acid group), vacuum impregnation 2.5 h.

[0085] 3. Electrostatic spraying: spraying voltage 48 kV, film thickness 28 μm, curing at 78 °C for 28 min.

[0086] Step 4: Preparation of self-healing functional layer 1. Microcapsule ratio: 16% of mechanically triggered microcapsules (MMS content 83%) + 6% of pH-triggered microcapsules (TEA-EDTA), fluorocarbon resin solid content 50%.

[0087] 2. UV curing: wavelength 370 nm, intensity 90 mW / cm 2 , time 4.5 min, film thickness 16 μm.

[0088] Example 3: Step 1: Preparation of zinc alloy substrate 1. Weigh 93.5% Zn, 5.2% Al, 1.1% Cu, 0.6% Mg, 0.15% Ce, melting temperature 440 °C, stirring speed 300 rpm, time 20 min.

[0089] 2. Die-casting pressure 95 MPa, mold preheating 155 °C, polished to Ra = 1.0 μm.

[0090] Step 2: Pretreatment of substrate surface 1. Sandblasting treatment: 60-mesh alumina, pressure 0.45 MPa, Ra = 4.8 μm.

[0091] 2. Chemical etching: 11% nitric acid + 3.5% hydrofluoric acid, etching time 35 s.

[0092] 3. Composite conversion film: 4.0% zinc phosphate + KH550 / KH560 compound (3:1) total concentration 4.5%, pH = 3.2, dipping time 11 min, film thickness 420 nm.

[0093] 4. Plasma grafting: N 2 / C 2 H 4 = 5.5:1, power 95 W, treatment 5.5 min.

[0094] Step 3: Preparation of slow-release anti-corrosion layer 1. Mesoporous synthesis: 5.5% CTAB, 1.2 mol / L ammonia water, pore size 11 nm on the surface / 8 nm on the bottom layer.

[0095] 2. Loading inhibitor: 7% benzotriazole derivative, dipping time 3.5 h.

[0096] 3. Electrostatic spraying: voltage 52 kV, film thickness 22 μm, cured at 82 °C for 26 min.

[0097] Step 4: Preparation of self-healing functional layer 1. Microcapsule ratio: 17% of mechanically triggered microcapsules (MPTMS 82%) + 7% of pH-triggered microcapsules (CaNa 2 EDTA80%).

[0098] 2. UV curing: wavelength 360 nm, intensity 110 mW / cm 2 , time 4.2 min, film thickness 19 μm.

[0099] Comparative Example 1: Compared with Example 1, the difference lies in that no Ce element is added to the zinc alloy matrix, and the remaining components and preparation steps are the same.

[0100] Comparative Example 2: Compared with Example 1, the difference lies in that mesoporous silica with a uniform pore size (pore size 10 - 12 nm, no gradient design) is used in the slow-release anti-corrosion layer, and the remaining steps are the same.

[0101] Comparative Example 3: Compared with Example 2, the difference lies in that the silane coupling agent in the phosphate-silane composite conversion film is replaced by methyltriethoxysilane (MTES), and the remaining steps are the same.

[0102] Comparative Example 4: Compared with Example 2, the difference lies in that the bottom pore size of the gradient mesoporous silica is adjusted to 12 - 15 nm, and the remaining steps are the same.

[0103] Comparative Example 5: Compared with Example 3, the difference lies in that the step of plasma grafting epoxy groups is cancelled in the surface pretreatment of the matrix, and the remaining steps are the same.

[0104] Comparative Example 6: Compared with Example 3, the difference lies in that only mechanically triggered microcapsules (pH-triggered microcapsule addition amount 0%) are used in the self-healing functional layer, and the remaining steps are the same.

[0105] Test Example 1: Verification of the synergistic effect of matrix modification - coating structure Test objects: Example 1, Example 2, Comparative Example 1, Comparative Example 2, Comparative Example 4.

[0106] The test steps are as follows: 1. Intergranular corrosion test (GB / T 10125 CASS 48 h): Place the sample in a salt spray chamber at a temperature of 35 ± 2 °C, 5% NaCl solution + 0.26 g / L CuCl 2 , spray pressure 70 kPa; take it out after 48 h, observe the grain boundary corrosion morphology with a super-depth-of-field microscope (KEYENCE VHX-7000), and rate it according to the ISO 10289 standard (grade 0: no corrosion; grade 4: severe corrosion).

[0107] 2. Mesoporous structure analysis (BET nitrogen adsorption - desorption): Take the powder sample of the slow - release anticorrosion layer and conduct nitrogen adsorption - desorption tests (Micromeritics ASAP2460) at 77K; calculate the pore size distribution through the BJH model and plot the adsorption - desorption isotherm.

[0108] 3. Salt spray corrosion propagation test (ASTM B117 720h): Pre - fabricate scratches (depth 50μm, width 200μm) on the coating surface; Salt spray conditions: 5% NaCl solution, continuous spraying at 35℃; After 720h, measure the maximum corrosion propagation width at the scratch edge (accuracy ±1μm).

[0109] The test results are shown in Table 1: Table 1: Sample Intergranular corrosion rating (0 - 4 levels) Mesoporous structure (pore size distribution) Corrosion propagation width (μm) Example 1 0 Bimodal (12.3nm / 6.8nm) 85.3 Example 2 0 Bimodal (13.7nm / 7.1nm) 92.7 Comparative Example 1 3 Bimodal (11.9nm / 7.0nm) 680.5 Comparative Example 2 0 Unimodal (10.8nm) 517.2 Comparative Example 4 0 Bimodal (14.2nm / 12.9nm) 608.9 From the test data in Table 1, it can be obtained that: In Comparative Example 1 without Ce, significant corrosion grooves (rating 3) appeared at the grain boundaries during the salt spray test, while the Example group containing Ce (rating 0) showed excellent intergranular corrosion resistance. This verifies the grain boundary purification mechanism of rare - earth cerium: Ce reacts preferentially with impurity elements such as Fe and Pb in the alloy melt to form high - melting - point CeFe 5 , CePb 3 and other stable compounds, effectively reducing the electrochemically active sites at the grain boundaries. At the same time, the oxidation products of Ce (such as CeO 2 ) adsorb on the substrate surface to form an initial passivation layer, further inhibiting the penetration of corrosive media along the grain boundaries.

[0110] The corrosion propagation widths of Comparative Example 2 (uniform pore size) and Comparative Example 4 (excessive bottom - layer pore size) (>500μm) are much larger than those of the Example group (<100μm), confirming that the gradient pore size design is the core innovation point of the slow - release anticorrosion layer. The large - pore - size (10 - 15nm) mesopores on the surface layer rapidly release high - concentration benzotriazole at the initial stage of corrosion, quickly neutralizing corrosive factors such as invading Cl - ; the small - pore - size (5 - 8nm) mesopores in the bottom layer limit the diffusion rate of the corrosion inhibitor through capillary action to achieve long - term slow release.

[0111] The excellent performance of the Example group (corrosion propagation width ≤100μm) stems from the cross - scale synergy between matrix modification (Ce purification) and coating structure (gradient mesopores). The grain boundary purification of Ce reduces the self - corrosion driving force of the matrix, while the gradient mesopores dynamically repair coating defects by sequentially releasing the corrosion inhibitor, and the two form a dual - protection network of "static barrier - dynamic repair".

[0112] Test Example 2: Interface Combination - Slow-release Dynamic Joint Verification Test Objects: Example 2, Comparative Example 3, Comparative Example 5

[0113] The test steps are as follows: 1. Pull-off Adhesion Test (ASTM D4541): Use a PosiTest AT-M automatic adhesion tester to bond a 20-mm diameter aluminum ingot to the coating surface; Pull vertically at a rate of 0.5 MPa / s and record the maximum bond strength (MPa).

[0114] 2. Dynamic Monitoring of Corrosion Inhibitor Release (HPLC): Immerse the coating sample in a 3.5% NaCl solution (25 °C) and take samples on the 1st, 7th, 15th, and 30th days respectively; Use an Agilent 1260 Infinity II HPLC system, a C18 chromatographic column (4.6×250 mm), with the mobile phase being methanol / water (60:40), a flow rate of 1.0 mL / min, and a detection wavelength of 254 nm; Quantitatively analyze the concentration of benzotriazole derivatives (mg / L).

[0115] The test results are shown in Table 2: Table 2: From the test data in Table 2, it can be obtained that: The bond strength of Comparative Example 3 (replaced with MTES silane) (4.7 MPa) decreased significantly compared to Example 2 (16.8 MPa), confirming the irreplaceability of amino silane (KH560). The amino group (-NH 2 ) of KH560 forms a chemical bridge with the matrix metal oxides (Al 2 O 3 / ZnO) through a covalent bond (Si-O-M), while MTES only relies on physical adsorption (van der Waals force). In addition, the amino group can also pre-react with the epoxy group of the subsequent epoxy resin to form a chemical cross-linking network penetrating the interface, further inhibiting coating peeling.

[0116] The slow-release curve of the corrosion inhibitor in Comparative Example 5 (plasma treatment cancelled) showed a "burst release - rapid decay" characteristic (89.3 mg / L on the 1st day → 6.8 mg / L on the 30th day), in sharp contrast to the steady release of Example 2 (73.2 → 22.3 mg / L). The epoxy groups (-CH 2 -CH(O)-CH 2-) It filled the micropores on the surface of the conversion film (SEM showed that the porosity decreased from 15% to 5%), and at the same time formed chemical anchoring points with epoxy resin. This densification not only enhanced the bonding strength, but also optimized the corrosion inhibitor release kinetics by restricting the medium penetration path. The data verified the dual functions of plasma treatment: interface strengthening (chemical bond) and structure regulation (physical barrier).

[0117] The "high → medium → low" three-stage release characteristics (73.2 → 48.5 → 22.3 mg / L) of the sustained-release agent in Example 2 revealed the synergistic effect of interface stability and mesoporous structure. The stable interface prevented the coating from cracking (the scratch propagation rate decreased by 83%), enabling the gradient mesopores to release the corrosion inhibitor as designed; while the sequential release of the corrosion inhibitor in turn fed back the interface integrity by inhibiting matrix corrosion.

[0118] Test Example 3: Verification of double-trigger self-healing efficiency Test objects: Example 3, Comparative Example 6.

[0119] The test steps are as follows: 1. Sample preparation: Prepare 5 parallel samples in each group, numbered S1 - S5 (Example 3), C1 - C5 (Comparative Example 6).

[0120] 2. Scratch making: Use a scratch tester (ASTM D7187 standard) to prefabricate a straight scratch with a width of 200 ± 10 μm on the coating surface, and the depth penetrates to the substrate (50 ± 5 μm).

[0121] 3. Repair environment simulation: Place the scratched samples in a thermostatic and humidified chamber (temperature 25°C, humidity 80%), spray an acidic solution with pH = 4.5 (simulating acid rain environment), spray once every 2 h, and continue for 24 h.

[0122] 4. Repair rate detection: Use a laser confocal microscope (Keyence VK-X3000) to measure the change in scratch width and calculate the repair rate: 5. Electrochemical performance test: Use an electrochemical workstation (Gamry 600+) to test the corrosion current density at the scratched area after repair in a three-electrode system (Tafel polarization curve method).

[0123] 6. pH response monitoring: Insert a micro pH electrode (Unisense PH-10) into the scratched area and record the change in pH value within 24 h in real time. The trigger threshold is set to pH ≤ 4.5 or ≥ 8.5.

[0124] The test results are shown in Table 3 as follows: Table 3: From the test data in Table 3, it can be obtained that: When physical scratches occur on the coating surface, the mechanically triggered microcapsules rupture rapidly to release the mercapto-siloxane prepolymer. The mercapto groups (-SH) in its molecular chain undergo oxidative cross-linking under the action of environmental oxygen and water molecules, and a dense hydrophobic silicon-oxygen network structure is formed within 30 minutes. This process rapidly blocks the penetration path of corrosive media through physical plugging. Meanwhile, the local microchemical environment changes caused by the damage (such as the pH ≤ 4.5 due to acidic corrosion) activate the pH-triggered microcapsules, and the EDTA derivative chelating agent is selectively released and combines with the exposed metal matrix surface Zn 2+ / Al 3+ to form a highly stable complex, effectively inhibiting the anodic dissolution reaction of the metal and blocking the continuous expansion of the corrosion reaction from the electrochemical level.

[0125] The core innovation of the dual-trigger mechanism lies in the dynamic coupling of physical repair and chemical passivation. The mechanically triggered repair agent achieves short-term emergency protection through the rapid film formation of siloxane, while the pH-triggered repair agent conducts long-term regulation for the corrosive microenvironment. The two construct a composite repair layer with both hydrophobic and corrosion inhibition functions through synergistic effects at the molecular level (such as the -SO 3 H group of EDTA forms hydrogen bond cross-linking with the -Si-O- network of mercapto-siloxane). Experimental data show that the corrosion current density of the dual-trigger system (0.87 - 1.05 μA / cm 2 ) is reduced by one order of magnitude compared with that of the single mechanically triggered system (9.85 - 12.30 μA / cm 2 ), verifying the deep inhibition effect of chemical passivation on electrochemical corrosion.

[0126] From the perspective of protection timeliness, the dual-trigger system exhibits multi-stage response characteristics. Within 0 - 2 hours after the damage occurs, the physical repair dominated by mechanical triggering completes the surface plugging; while in the 2 - 24-hour stage, the chelating agent released by pH triggering continuously neutralizes the catalytic ions such as Fe 3+ in the corrosion products to prevent them from accelerating metal oxidation. This sequential synergistic mechanism breaks through the technical bottleneck of the traditional single repair agent of "effective in the short term and ineffective in the long term", making the impedance modulus of the repaired coating (1.05 - 1.32×10 6 Ω·cm 2 ) recover to more than 90% of the original coating, providing an innovative solution for the long-term service of a corrosion-resistant self-repairing metal fastener in a complex corrosion environment.

[0127] Although embodiments of the present invention have been shown and described, it will be understood by those of ordinary skill in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A corrosion-resistant self-repairing metal fastener, characterized in that: include: Zinc alloy substrate; A composite coating covering the surface of a substrate, wherein the composite coating comprises, from the inside to the outside: Nano passivation layer, phosphate-silane composite conversion film; A slow-release anticorrosion layer, a water-based epoxy resin layer containing mesoporous silica particles and a pH-responsive corrosion inhibitor; The self-repairing functional layer comprises a fluorocarbon resin layer containing mechanically triggered microcapsules and pH triggered microcapsules.

2. A corrosion-resistant self-repairing metal fastener according to claim 1, characterized in that: The zinc alloy matrix includes the following components in percentage by mass: Al4.5~5.5%, Cu0.8~1.2%, Mg0.4~0.6%, Ce0.05~0.2%, and the balance is Zn and inevitable impurities.

3. The corrosion-resistant self-repairing metal fastener according to claim 1, characterized in that: The nano passivation layer includes the following components in percentage by weight: Zinc phosphate 2.0-4.0%, silane coupling agent 3.0-5.0%, and the balance is deionized water.

4. The corrosion-resistant self-repairing metal fastener according to claim 3, characterized in that: The silane coupling agent is selected from at least one of γ-aminopropyltriethoxysilane and γ-glycidyloxypropyltrimethoxysilane.

5. The corrosion-resistant self-repairing metal fastener according to claim 1, characterized in that: The sustained-release anticorrosive layer comprises the following components in percentage by weight: 60-75% of waterborne epoxy resin matrix, 15-25% of gradient pore size mesoporous silica particles, 3-8% of benzotriazole derivative corrosion inhibitor, and the balance of dispersing aids and solvents.

6. The corrosion-resistant self-repairing metal fastener according to claim 1, characterized in that: The self-repairing functional layer comprises the following components in percentage by weight: Fluorocarbon resin matrix 65-80%, mechanically triggered microcapsules 12-18%, pH triggered microcapsules 4-8%, photoinitiator 1-3%, and the balance is leveling agent and solvent.

7. The corrosion-resistant self-repairing metal fastener according to claim 6, characterized in that: The content of the mechanically triggered microcapsule is mercaptosiloxane prepolymer, and the content of the pH-triggered microcapsule is EDTA derivative chelating agent.

8. A method for preparing a corrosion-resistant self-repairing metal fastener, used for preparing a corrosion-resistant self-repairing metal fastener according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Matrix preparation: The Zn-Al-Cu-Mg-Ce alloy is melted and die-casted at 420-450°C with a molding pressure of 80-100 MPa; (2) Substrate surface pretreatment: sandblasting, chemical etching, phosphate-silane composite conversion film treatment and plasma grafting are performed in sequence; (3) Preparation of sustained-release anticorrosive layer: The gradient pore size mesoporous silica loaded with benzotriazole derivatives is dispersed in water-based epoxy resin, coated on the substrate surface by electrostatic spraying, and cured at 75-85°C for 25-35 minutes; (4) Preparation of self-healing functional layer: The mechanically triggered microcapsules and pH-triggered microcapsules are uniformly dispersed in the fluorocarbon resin, coated on the surface of the sustained-release anti-corrosion layer, and cured under ultraviolet light for 4 to 6 minutes to form the final coating structure.

9. The method for preparing a corrosion-resistant self-repairing metal fastener according to claim 8, characterized in that: The step of pre-treating the substrate surface comprises: The sandblasting process uses 60-100 mesh alumina particles and the pressure is controlled at 0.3-0.5 MPa; The chemical etching treatment uses a mixed solution of 8 to 12 vol% nitric acid and 2 to 4 vol% hydrofluoric acid, and the etching time is 20 to 40 seconds; During the preparation of the phosphate-silane composite conversion film, the pH value of the sol is controlled at 3.0 to 4.0, the reaction temperature is 55 to 65°C, and the immersion time is 8 to 12 minutes; The plasma grafting is carried out in a nitrogen / ethylene mixed gas atmosphere with a volume ratio of 4 to 6:1, a power of 80 to 120 W, and a treatment time of 4 to 6 minutes to graft epoxy groups on the surface of the conversion film.

10. The method for preparing a corrosion-resistant self-repairing metal fastener according to claim 8, characterized in that: In the step of preparing the sustained-release anticorrosion layer, the electrostatic spraying voltage is controlled at 45-55 kV, the film thickness is 20-30 μm, and the heating is uniform during the curing process; In the step of preparing the self-repairing functional layer, the UV curing wavelength is controlled at 360-370 nm, and the irradiation intensity is 80-120 mW / cm 2 .

Citation Information

Cited By

  • Corrosion-resistant high-strength epoxy resin oily primer and preparation method thereof

    CN120648337A

  • Environment-friendly high-performance biological new energy fuel and preparation method thereof

    CN120924321A

  • Environment-friendly high-performance bio-new energy fuel and preparation method thereof

    CN120924321B

  • Resin-based brake pad for new energy and preparation method of resin-based brake pad

    CN121160023A

  • A resin-based brake pad for new energy and a preparation method thereof

    CN121160023B